THE INFLUENCE OF BRAND IMAGE AND SCHOOL FEES ON STUDENT DECISIONS TO STUDY AT FATIMA 2 SARUDIK CATHOLIC HIGH SCHOOL CENTRAL TAPANULI. T.A 2023/2024 - Kartini Katarina Nababan; Anton Luvi Siahaan; Pdt. Paulina H. N. (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2026)
This study aims to determine the effect of Brand Image and School Fees on Student Decisions at Fatima 2 Catholic High School in Sarudik, Central Tapanuli. This type of research is quantitative research using SPSS'22 testing media. The population in this study is based on the number of T.A 2023/2024 students totaling 184 students. This study uses probability sampling techniques; simple random sampling and using the Slovin formula with an error rate of 10% to obtain a sample of 65 students. Data collection techniques in this study used interviews, questionnaires, and documentation. The data analysis method used in this study, researchers used multiple regression analysis and the coefficient of determination (R2). Based on the results of the study, it show that there is a positive and significant influence on students' school decisions at Fatima 2 Catholic High School in Sarudi, Central Tapanuli. School fees have a positive and significant effect on student decisions at Fatima 2 Catholic High School in Sarudi, Central Tapanuli. Brand Image and school fees simultaneously have a positive and significant effect on student school decisions at Fatima 2 Catholic High School in Sarudi, Central Tapanuli.